Terminally coordinated AsS and PS ligands. - Balázs, G; Green, J; Scheer, M (2006)
The terminal AsS and PS complexes [(N(3)N)W(ES)] (N(3)N=N(CH(2)CH(2)NSiMe(3))(3); E=P (3), As (4)) were synthesised by reaction of [(N(3)N)W[triple chemical bond]As] and [(N(3)N)W[triple chemical bond]P], respectively, with cyclohexene sulfide. Both complexes present very short W--E and E--S bond lengths. The bonding was investigated by density functional theory (DFT) calculations using the fragment calculation method and natural bond orbital (NBO) analysis. According to the fragment analysis, in which the complexes were separated in an ES and a (N(3)N)W fragment, the bonding in complexes 3, 4 and [(N(3)N)W(SbS)] (5) is realised over a set of two sigma (1 sigma and 2 sigma) and two degenerate pi molecular orbitals (MOs) (1 pi and 2 pi). The 1 sigma MO is a bonding MO extended over the N(ax)-W-E-S core, whereas the 2 sigma MO is localised mainly on the E-S fragment. The 1 pi set is a E-S localised bonding molecular orbital, whereas the 2 pi set is in phase with respect to W-E but in antiphase with respect to E-S. Both methods indicate bond orders around two for both the E--S and the W--E bonds. The polarity of the complexes was examined by Hirshfeld charge analysis. This shows that complexes 3 and 4 are only slightly polarised, whereas 5 is moderately polarised toward the sulphur. As suggested by the computational results, the pi system in complexes 3-5 is best described by two three-centre four-electron bonds.